Phase-field Simulation and Experimental Validation on Microstructure Evolution of Fe-1.5% C Alloy - Gao Ting, Li Wanming, Wang Zhanzhong (Teshugang)
Two-dimensional and three-dimensional phase field models were constructed using KKS model to investigate the three-dimensional microstructure growth mechanism of Fe-1.5% C alloy during solidification.Through high-temperature laser confocal technology， in-situ observation of the binary alloy structure is achieved， and the observed results are compared with simulation data to verify the accuracy of the phase-field simulation. The results indicate that the length of dendrite growth is significantly different at different cooling rates.Further analysis reveals that the three-dimensional phase-field simulation exhibits higher accuracy in predicting dendrite growth during alloy solidification compared to two-dimensional simulations. When the cooling rate is 2 000 ℃/min， the primary dendrite growth length in the three-dimensional simulation reaches 0.6 µm， which is close to the experimental value of 0.5 µm. However， when the cooling rate increases to 3 000 ℃/min， the three-dimensional simulation result is 1.4 µm， highly consistent with the experimental observation value of 1.45 µm. Additionally， the anisotropy strength plays a decisive role in dendrite growth， with a critical value of 0.045 determining the stability of dendrite growth in both two-dimensional and three-dimensional spaces. Once this critical value is exceeded， it will lead to the dendrite instability